Processes, meanings and effects around the official cataloging of disabilities in women - Gómez Bernal, Vanessa (Nómadas. Critical Journal of Social and Juridical Science, 2013)
This article analyzes the process, the meanings and effects involved in oficial cataloging as part of disability in women. People with disabilities are part of a reference field governed by the logic of institutionalization: the full recognition of their status as “persons with disabilities”, recognizing the need for acces to certain social resources is needed to asses their condition diagnosed and degree of disability. Once diagnosed their degree of disability shall be opened various procedures considered suitable for inclusion. For women, it is understood that in the official cataloging as “disabled” significantly influences the conceptualization of gender as a device that generates power relations.
Keywords: cataloging; disability; gender; institutionalization